2022
DOI: 10.3389/fneur.2022.1000889
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative susceptibility mapping (QSM) and R2* of silent cerebral infarcts in sickle cell anemia

Abstract: Silent cerebral infarction (SCI) is the most commonly reported radiological abnormality in patients with sickle cell anemia (SCA) and is associated with future clinical stroke risk. To date, there have been few histological and quantitative MRI studies of SCI and multiple radiological definitions exist. As a result, the tissue characteristics and composition of SCI remain elusive. The objective of this work was therefore to investigate the composition of segmented SCI lesions using quantitative MRI for R2* and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…To date, studies that have used QSM and R2* relaxometry analyses for cerebrovascular diseases have adopted a cross-sectional design. 12–14 In these studies, ischemic lesions demonstrated increased magnetic susceptibility and decreased R2* values compared with normal-appearing white matter areas, suggesting a lower myelin content within the ischemic lesion. However, the tissue composition of iron and myelin could not be cross-sectionally inferred because the distribution of iron and myelin differs in each anatomic region of the brain.…”
mentioning
confidence: 79%
“…To date, studies that have used QSM and R2* relaxometry analyses for cerebrovascular diseases have adopted a cross-sectional design. 12–14 In these studies, ischemic lesions demonstrated increased magnetic susceptibility and decreased R2* values compared with normal-appearing white matter areas, suggesting a lower myelin content within the ischemic lesion. However, the tissue composition of iron and myelin could not be cross-sectionally inferred because the distribution of iron and myelin differs in each anatomic region of the brain.…”
mentioning
confidence: 79%
“…There are a range of dipole inversion methods to choose from and, after comparison of several state‐of‐the‐art direct and iterative methods, iterative Tikhonov regularisation (Karsa et al, 2020), non‐linear total variation (TV; Milovic et al, 2018) and weak harmonic QSM (WH‐QSM) (Milovic et al, 2019) were selected. Iterative Tikhonov was chosen for its applicability to head (and neck) imaging (Karsa et al, 2020) and its use in clinical QSM research (Murdoch, Stotesbury, Kawadler et al, 2022; Murdoch, Stotesbury, Hales et al, 2022). Total variation‐based approaches were shown to be the most accurate in the QSM Challenge 2.0 (Bilgic et al, 2021) and non‐linear TV (FANSI), in particular, was chosen because it scored the highest in Stage 2 of the Challenge.…”
Section: Methodsmentioning
confidence: 99%